VAR implementation and soccer team performance: a comparison between the 2014 and 2018 World Cups - Costa Oliveira, M. A.; Dambroz, F.; Santos, R.; Moniz, F. (Journal of Physical Education and Sport, 2021)
Introduction: In soccer, referees and assistants must make fast and accurate judgments based on the game rules. As an attempt to minimize refereeing errors and reduce their impact on match outcomes, the video assistant referee (VAR) was introduced on the game. The VAR is a technological apparatus that enables referees to review their decisions on video. The interruptions for VAR checking have an indefinite duration and occur randomly during the match. Therefore, disciplinary aspects and technical and physical performances of the teams are potentially susceptible to changes. Objective: The purpose of the present study was to verify whether the implementation of the VAR influenced disciplinary sanctions as well as the physical and technical performance of the teams participating in the 2018 FIFA World Cup, when compared to the previous edition (2014), in which the VAR was not used. Methods: The sample was comprised of matches played in the 2014 (n = 57) and 2018 (n = 59) editions of the FIFA World Cup. Teams` te chnical and physical performances and match data were compared between both tournaments. Results: Findings indicated that technical performance was influenced by the implementation of the VAR, as teams displayed reduced number of passes and increased percentage of accurate passes. Also, results showed an increase in average total distance covered and a decrease in the number of individual and total sprints per team, in the tournament in which the VAR was employed. Analysis of match data indicated a reduction in the number of offsides, fouls and red cards, more penalties and yellow cards, as well as more additional time in both halves and in the whole match. Conclusions: The implementation of the VAR prompted changes in the disciplinary aspects of matches and influenced the number of high-speed actions and technical actions performed by the teams, despite the increased accuracy in the execution of technical actions.